Periodontal (formerly type VIII) Ehlers–Danlos syndrome: Description of 13 novel cases and expansion of the clinical phenotype. Issue 2 (29th April 2021) - El Chehadeh, Salima; Legrand, Anne; Stoetzel, Corinne; Geoffroy, Véronique; Billon, Clarisse; Adham, Salma; Jeunemaître, Xavier; Jaussaud, Roland; Muller, Jean; Schaefer, Elise; Benistan, Karelle; Gaertner, Sébastien; et al.
Abstract: Periodontal Ehlers–Danlos syndrome (pEDS) is a rare condition caused by pathogenic variants in the C1R and C1S genes, encoding subunits C1r and C1s of the first component of the classical complement pathway. It is characterized by early‐onset periodontitis with premature tooth loss, pretibial hyperpigmentation and skin fragility. Rare arterial complications have been reported, but venous insufficiency is rarely described. Here we report 13 novel patients carrying heterozygous pathogenic variants in C1R and C1S including three novel C1S variants ( c.962G > C, c.961 T > G and c.961 T > A). In addition to the pEDS phenotype, three patients and one relative displayed widespread venous insufficiency leading to persistent varicose leg ulcers. One patient suffered an intracranial aneurysm with familial vascular complications including thoracic and abdominal aortic aneurysm and dissection and intracranial aneurysm rupture. This work confirms that vascular complications can occur, although they are not frequent, which leads us to propose to carry out a first complete non‐invasive vascular evaluation at the time of the diagnosis in pEDS patients. However, larger case series are needed to improve our understanding of the link between complement pathway activation and connective tissue alterations observed in these patients, and to better assess the frequency, type and consequences of the vascular complications. Abstract : Periodontal Ehlers–Danlos syndrome (pEDS) is a rare condition caused by autosomal dominant pathogenic variants in C1R and C1S, characterized by early‐onset severe periodontitis with premature tooth loss, easy bruising, pretibial hyperpigmentation and skin fragility. We report 13 novel pEDS patients carrying heterozygous pathogenic variants in C1R and C1S . In addition to the main pEDS clinical signs, including complete tooth loss before the age of 30 years in three patients, three patients and one relative displayed widespread venous insufficiency leading to persistent leg ulcers. One patient suffered an intracranial aneurysm with familial vascular complications including aortic dissection and intracranial aneurysm rupture in several relatives. Brain MRI showed in two patients periventricular white matter hyperintensities. Rare vascular complications exist including venous insufficiency and arterial dissection that can be fatal. More cases with enhanced vascular characterization are required in order to determine if a systematic vascular monitoring, including both arterial and venous assessment, would be recommended.